Testing the Effect of Quality Reports on the Health Plan Choices of Medicare Beneficiaries - Jennifer D. Uhrig; Pamela Farley Short (SAGE Publishing, 2002)
This article describes a laboratory experiment that used a convenience sample of 225 Medicare beneficiaries to test the effects of comparative quality information on plan choice. Providing information about quality did not significantly influence the choice between Original Medicare and a health maintenance organization (HMO), but did affect the choice of HMO. Results from this experiment suggest that information about plan quality may not be effective in encouraging beneficiaries to leave Original Medicare and join HMOs that are rated high in quality. Furthermore, beneficiaries choosing among HMOs were not inclined to select a low-cost HMO, even when it was rated higher in quality. Implications for policy are discussed.